L’adaptation du Pastor Fido de Fanshawe par Elkannah Settle (1676) - Denis Lagae-Devoldère (Etudes Epistémè, 2003)
Based on a close comparative reading of two English adaptations of Guarini’s Pastor Fido, Richard Fanshawe’s version (1647) and that of Elkannah Settle (1676), this article sets out to identify some of the main structural, linguistic and aesthetic differences and similarities between the two texts. Such variations are held to be significant in terms of the aesthetics of the Restoration period, particularly as far as dramatic tastes and production are concerned.